Electricity efficiency of auxiliary power systems in coal thermal power plant - Mujanović, Azrina (Array, 2020)
Renewable energy sources such as hydro, wind and solar energy are taking an increasing share in the electricity mix. However, electricity production from thermal power plants is independent of the weather conditions and is still important as a back-up power source to renewable energy sources. Given the fact that the electricity market is open, it is clear that each MWh is important. Therefore, auxiliary power systems as a part of thermal power plants should be also energy efficient. The main aim of the presented research was to investigate the efficient operation of different consumers in the auxiliary power system in the old-dated thermal power plant ‘’Tuzla’’ depending on different power at generator output. The performed analysis identified consumers suitable for electricity efficiency improvement giving results of power savings obtained on modestly available measurements and old-date technical documentation. Following obtained results, some recommendations for improving electricity efficiency were proposed with a rough calculation of possible savings. Measurements of auxiliary power system consumption depending on power at generator output in new thermal power plant ‘’Stanari’’ was presented. Future trends and directions in thermal power plant automation were also discussed.